Forecasting and Criminal Justice Policy and Practice - Sabol, William J. (American journal of criminal justice, 2022)
We address the organization of criminal justice forecasting and implications for its use in criminal justice policymaking. We argue that the use of forecasting is relatively widespread in criminal justice agency settings, but it is used primarily to inform decision-making and practice rather than to formulate and test new policy proposals. Using predictive policing and prison population forecasting as our main examples of the range of forecasting methods adopted in criminal justice practice, we describe their uses, how their use is organized, and the implications of the organizational arrangements for the transparent, reviewable, and consensual use of forecasting. We point out that both prison population forecasting and predictive policing have long histories that have led to advances in methodology. Prison population forecasting has generally become embedded in budget decision-making processes that contribute to greater transparency in method and applications. Predictive policing has been less transparent in method and use, partly because the methods are more complicated and rely on larger amounts of data, but it generally has not be used in ways to foster community engagement and build public support. Concerns about the legitimacy of its use persist.